Pemberdayaan Masyarakat melalui Ekonomi Kreatif dengan Produk Permen Jelly Labu Siam di Desa Mendale Aceh Tengah: Pengabdian - Kamarudin, Anna Permatasari; Suknah, Suknah; Basyirah, Basyirah; Ramiati, Ramiati; Fatma, Mawarni; Amna, Amna; Aswad, Hajar; Zainuddin, Zainuddin; Delvia, Delvia; Mah, Hijrah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Mendale Village is one of the tourist villages in Central Aceh. So it is always crowded with tourists visiting Laut Tawar Lake. The purpose of this Community Service is to empower the people of Mendale Village through the creative economy with chayote jelly candy products. It is hoped that the processed chayote can become one of the culinary specialties of Mendale Village and can also provide additional income for the community. Marketing can be done around tourist attractions around Mendale Village. The methods used for Partners are lectures, demonstrations and training. There are 20 Partners consisting of PKK Cadres and other mothers from the general public. Partners are given a Pre-Test and Post-Test to determine the increase in knowledge that occurs during the implementation of the program. At the end of the implementation, Partners are also given an Implementation Evaluation Form. The results of the analysis show that Partners' knowledge has increased, especially in the fourth statement ('Chayote can be processed into various products with various flavors (sweet, salty, spicy and savory') there has been an increase of 85%. This shows that Partners have optimal knowledge about processing chayote into jelly candy. As many as 100% of Partners stated 'Strongly Agree' that the training material is easy to understand. Statement This training is useful and I will attend a similar event if it is held again received an assessment from Partners 'Strongly Agree' each of 90%.